A review of the socio-economic advantages of textile recycling. (1st May 2019) - Leal Filho, Walter; Ellams, Dawn; Han, Sara; Tyler, David; Boiten, Valérie Julie; Paço, Arminda; Moora, Harri; Balogun, Abdul-Lateef
Abstract: The textile/apparel industry is of great importance to the economy in terms of trade, employment, investment and revenue all over the world. This sector is however characterised by substantial losses, due to production excesses on the one hand, and the "throw away" culture on the other. This state of affairs suggests that textile recycling is needed. Apart from the environmental and ecological advantages which can be brought about by the re-use and recycling of textiles, there are many benefits of a socio-economic nature. This paper analyses current trends on textile recycling, the barriers impeding greater recycling, and outlines the socio-economic advantages of moving towards a circular economy. Some examples of on-going initiatives are discussed, together with some of the measures that may be used to further reduce the current waste deriving from the apparel sector. Graphical abstract: Image 1084 Highlights: The apparel industry is economically important all over the world. Production excesses lead to losses, so textile recycling is needed. There are socio-economic, environmental and ecological advantages brought about by recycling of textiles. There are measures that may be used to reduce the current waste deriving from the apparel sector.